2017
DOI: 10.1097/njh.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Heart Failure Knowledge Is Necessary but Not Sufficient to Ensure Engagement With Patients in Self-care Maintenance

Abstract: The chronic illness literature suggests that patient–informal caregiver dyads who are relationally oriented (share decisions and activities) are more efficient and effective than those who are not. But this is currently unknown in heart failure (HF). Our aim was to examine differences between individually and relationally oriented HF dyads relative to patient symptom management scores. This was a cross-sectional study of 55 dyads (spousal/adult child/relative) analyzed using Actor-Partner Interdependence Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Importantly, our findings are similar to another recent dyadic study in HF that found that better patient knowledge was important to self-care adherence, but only in concert with patient and caregiver agreement on how HF disease management was handled within the dyad. 55…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our findings are similar to another recent dyadic study in HF that found that better patient knowledge was important to self-care adherence, but only in concert with patient and caregiver agreement on how HF disease management was handled within the dyad. 55…”
Section: Discussionmentioning
confidence: 99%
“…The next mixed method study [25][26][27] was prospectively designed to describe dyadic engagement in HF self-care. We enrolled 78 mixed (spousal, adult child, other) dyads.…”
Section: Study 4: Dyadic Mutual Engagement and Hypothesis Testingmentioning
confidence: 99%
“…This suggests to us that we need to examine the role of dyadic congruence or agreement on type more closely if we expect caregivers to engage in daily self-care behaviors. 25…”
Section: Study 4: Dyadic Mutual Engagement and Hypothesis Testingmentioning
confidence: 99%
“…HF patients usually have a partner with whom they make day-to-day decisions about symptom management but also about diet and how to deal with worsening symptoms. Dyadic HF research has shown that good relationships with a partner and other people [ 12 , 13 ], knowledge regarding HF of each member of the dyad [ 14 ], congruence in symptom assessment, and agreement on who is providing self-care [ 15 ] influence HF behavior and may determine a patient’s outcome. Within this dyad, caregivers influence patient self-care and patients influence caregiver’s contribution to self-care.…”
Section: Introductionmentioning
confidence: 99%